Impact of enhanced personal protective equipment on colonoscopy performance during the COVID-19 pandemic - Teh, Kevin Kim Jun; Tay, Shu Wen; Chen, Kaina; Koh, Samantha Jingyun; Wong, Yu Jun; Kwek, Andrew Boon Eu; Li, James Weiquan; Fock, Kwong Ming; Teo, Eng Kiong; Ang, Tiing Leong; Tan, Malcolm Teck Kiang (Endoscopy International Open, 2020)
Background and study aims Using personal protective equipment (PPE) can reduce risk of disease transmission. During the COVID-19 pandemic, enhanced PPE (EPPE) is recommended when performing endoscopy. We aimed to evaluate the impact of EPPE on colonoscopy performance when compared to standard PPE (SPPE).Patients and methods A review of electronic medical records and endoscopy reports of consecutive patients who underwent colonoscopy during two similar one-month time periods (in 2019 and during the COVID-19 pandemic in 2020) was performed. SPPE was used in 2019 and EPPE was used in 2020. Patient clinical data and procedure-related information were captured and analyzed. The primary outcomes were time to cecum (TTC) and total procedure time. Secondary outcomes were adenoma detection rate (ADR), polyp detection rate (PDR) and cecal intubation rate (CIR). Statistical analysis was performed using STATA v16.1.Results Two hundred and forty-seven colonoscopy procedures were analyzed. Baseline demographics and indications for colonoscopy of patients in both groups were similar. There were no significant differences in median TTC (10.0 vs 10.0 min, P = 0.524) or total procedure time (22.5 vs 23.0 min, P = 0.946) between colonoscopy performed in SPPE and EPPE. The ADR, PDR and CIR were also similar.Conclusion Our findings suggest that use of EPPE does not affect colonoscopy performance.